BEYOND THE LECTURE HALL: THE TRANSFORMATIVE POWER OF INDUSTRY-EXPERIENCED FACULTY MEMBERS OF BUSINESS SCHOOLS IN MALAYSIAN HIGHER EDUCATION INSTITUTIONS - A CONCEPTUAL PERSPECTIVE - Abu Bazar, Megat Muzzamir Megat; Ismail, Noor Adibah; Mohd Azmi, Mohamad Alif Azmiezal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The presence of industry experience in business education is becoming more crucial, yet research on its impact, particularly within Malaysian higher education institutions (HEIs), remains limited. While practical training is widely acknowledged in STEM disciplines, its role in shaping business educators' teaching effectiveness and improving student learning outcomes has not been extensively examined. Over the years, Malaysia’s job market has undergone significant changes, with entrepreneurship, freelancing, and digital businesses becoming more common due to economic shifts. As traditional career paths become less stable, business students must gain more than just theoretical knowledge. Exposure to industry practices through experienced educators can help them develop the skills and mindset needed to succeed in today’s evolving business landscape. This paper explores how integrating industry knowledge into academic settings benefits both educators and students. By reviewing existing studies and theoretical perspectives, the discussion highlights the value of experiential learning and industry collaboration in equipping students with real-world problem-solving abilities. Strengthening the connection between universities and industry practitioners is essential to ensure business education in Malaysia remains relevant, adaptable, and aligned with the country’s economic needs.